Elevated serum beta-2 microglobulin level predicts short-term poor prognosis of patients with de novo acute omicron variant COVID-19 infection - Gong, Shengping; Ma, Ruishuang; Zhu, Ting; Ge, Xiaoqin; Xie, Rongrong; Tao, Qingsong; Shi, Cong (Frontiers in Cellular and Infection Microbiology, 2023)
Background The devastating coronavirus disease of 2019 (COVID-2019) epidemic has been declared a public health emergency, resulting in a worldwide pandemic. The omicron variety is the most common epidemic mutant strain in the globe. Serum beta-2 microglobulin (β2-MG) is associated with endothelial cell injury and has value in monitoring the progression of inflammation in infected individuals. Nonetheless, the potential functions of β2-MG in omicron remain elusive. Methods To investigate the prognostic value of serum β2-MG levels at diagnosis, we retrospectively analyzed a cohort of 240 people with omicron. Over the course of 65 days, all patients were monitored, and death was the primary outcome. Patients were allocated to two groups: those with high and low β2-MG levels. The Kaplan–Meier method was used to examine OS, and the log-rank test was used to compare them. Univariate and multivariate Cox hazard models were used to determine the prognostic significance. Results Our results revealed that β2-MG was significantly elevated in omicron. β2-MG levels in severe patients were higher than in mild-to-moderate patients, and the difference was statistically significant. Timely, interleukin-6 (IL-6) and interleukin-10 (IL-10) were observed to be significantly increased in individuals exhibiting elevated levels of β2-MG. In addition, patients exhibiting elevated levels of β2-MG demonstrated a statistically significant decrease in overall survival (OS, P < 0.0001). An elevated β2-MG level (≥4.72 mg/l) was found to be an independent, adverse prognostic factor for OS in omicron patients, according to multivariate Cox proportional hazards regression analysis (P = 0.001). Conclusion Serum β2-MG level at initial diagnosis was significantly correlated with omicron severity and prognosis. Thus, we propose that β2-MG may be an independent poor additional prognostic factor in patients with omicron.